The effect of detraining on cardivascular responses in young table tennis players - Katsikadelis, M.; Pilianidis, T.; Mantzouranis, N.; Fatouros, I.; Aggelousis, N. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The purpose of this study was to evaluate the effect of the 20-day detraining on cardiovascular responses. Ten (n=10) adolescent players (5 boys & 5 girls), aged 10.8±2.3yrs with body mass 47.5±14kg and stature 1.50±1.5cm completed a 10-week Multiball interventional training program and they were reevaluated after a 20-day detraining period (pre-post). Measurements of Maximum Oxygen uptake (VO2max), Lactate concentration (La) and Maximum Heart Rate (HRmax) were evaluated during the progressive exercise test to exhaustion on a motorized treadmill (S 2500, Tecmachine, Andrezieux-Boutheon, France). Pulmonary gas exchange and ventilation was recorded by means of Filmate Pro spirometer (Cosmed, Rome, Italy). The Anova analysis of variance with two repeated factors (group & measurements) and Bonferroni post hoc test were applied in order to compare the effect of different protocols on the players' performance. The statistical significance was defined at 5% (p<0.05). It was derived from the results that the abstention from table-tennis training causes a decline in the players' VO2max (mean pre: 47.4 ± 2.64ml.min.kg-1 - post: 43.4 ± 2.45ml.min.kg-1). Also a tendency for value restoration of La (mean pre: 8.06 ± 1.07mmol.l-1 - post: 7.83± .964mmol.l-1) and HRmax (mean pre: 203± 2.79b.min-1 - post: 202± 2.52b.min-1) to the original ones was observed. Conclusively, the Multiball training method can cause noticeable adaptations to the physiological abilities of adolescence table-tennis players which are maintained after a 20-day interruption of the training procedures.